Model characteristics of combat at elite male karate competitors - Koropanovski, N.; Jovanovic, S. (Serbian Journal of Sports Sciences, 2007)
In karate, so far, nobody has set any serious completed system of following and analyzing of sports competitions, which would enable a complete review of technical and tactical features of contestants. We could search for the reason in the objective complexity of sports competitions, in identifications of technical and tactical elements, as well as in the way of their utilization for the analysis of competitive activity. The problem of this work deals with research in competitive activity of karate competitors. The orientation for this research problem took rise from the assumption that results of research in competitive activity are important for planning and programming of training process because sports change intensively under the influence of modification of competitive rules. Research subject refers to technical and tactical characteristics of sports competition in karate. Research objective is determining of model characteristics of sports competitions by the analyses of a certain number of fights at high-quality European and world competitions in the past few years. The sample for analysis consists of 55 final competitions, i.e., 110 contestants in man competition at European championships in Bremen (Germany) 2003, Moscow (Russia) 2004, Tenerife (Spain) 2005, and at World championships in Madrid (Spain) 2002 and Monte Ray (Mexico) 2004. Based on descriptive statistical analysis, gained from the measuring of frequency of occurrence which is expressed from the aspect of relative and absolute value, and also by analyzing of quantitative differences, by using of individual and collective method - General Linear Model (GLA), we came to the conclusion that there is statistically significant difference in quantitative frequency of structural elements of sports competitions.